2011
DOI: 10.1007/s13139-011-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Bone Scan Findings after High-Intensity Focused Ultrasound (HIFU) Treatment

Abstract: Purpose This study aims to examine the findings of 99m Tcdiphosphonate bone scans in cancer patients with a history of HIFU treatment. Methods Bone scan images of patients with a history of HIFU treatment for primary or metastatic cancer from January 2006 to July 2010 were retrospectively reviewed. Cases of primary bone tumor or HIFU treatment reaching only the superficial soft tissue layer were excluded. Results Bone scan images of 62 patients (26 female, 36 male; mean age 57±9 years) were studied. HIFU treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
“…Forty-four studies reported on the clinical use of HIFU (7,(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) to treat liver lesions , while 19 series were found on HIFU treatment for pancreatic cancers (6,(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73) and 4 studies included patients suffering from both liver and pancreatic cancers (74)(75)(76)(77), reporting on a total of 1,682 and 823 cases for the liver and pancreas, respectively. However, the real number of patients who benefited from HIFU treatment is much larger, since a recent review article from Zhou reported on over 3,000 cases of advanced pancreatic cancer treated with HIFU alone or in combination with chemotherapy (CHT) or radiotherapy (RT) (78).…”
Section: Study Selection and Level Of Evidencementioning
confidence: 99%
“…However, MRgHIFU in highly perfused tumors is challenging because higher energy is required to compensate for the cooling of the tissues induced by blood flow, called the heat sink effect [16]. Subsequently, critical side effects are produced, such as skin or bone burning, post focal energy deposition or side lobe effects [17][18][19]. Jung et al [20] reported a significant number of adverse effects occurring after HIFU treatment of hepatic tumors, hepatic metastasis and pancreatic cancers such as skin burning, edema, and, in all patients, pain.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, even when US energy is concentrated to the focal point, it can also be deposited along the US beam in front or behind the focus point and cause severe side effects such as skin and bone burning. 8,[12][13][14] Furthermore, given a treatment planning, interpatient variation in the volume and shape of the lesion may be difficult to control and to reproduce. 15 The ablative effects of HIFU are due to the focusing of high energy beams in a small region on the order of the wavelength, i.e.…”
Section: Introductionmentioning
confidence: 99%